Analysis of the Effect of Gender, High School Origin, Middle School Department, College Motivation on Academic Achievement of Students of Accounting and Finance Department: Case Study on One of Private University in Indonesia - Michael Angelus; Armanto Witjaksono (Bina Nusantara University, 2022)
This research aims to know the learning patterns and student’s abilities in education performance by identify and analyze the influence of gender, the high school origin, high school programs, motivation on academic achievement. The methods of data collection are carried out through the following methods of questionnaires, literature studies. This study is quantitative explanatory and retrieves important accounting items. Based on the data analysis was conducted, the results showed that gender, high school programs, college motivation are not significantly affected in the GPA While the origin of high school significantly affects the GPA. This study suggested that future studies adopt other methods of data analysis and take the dependent variable other than academic achievement.